Coal-based hard carbon negative electrode material and preparation method and application thereof
By regulating the ratio of the platform area to the slope area and specific surface area of coal-based hard carbon negative electrode materials, the problem of difficult to balance the charging and discharge capacity of traditional coal-based materials in sodium ion batteries and the first week of Coulomb efficiency in sodium ion batteries is achieved, and the high first week of reversible capacity and first week of Coulomb efficiency are improved.
Patent Information
- Application Number
- CN202411856378.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-17
- Publication Date
- 2025-03-21
AI Technical Summary
Traditional coal-based materials are difficult to take into account both the charge and discharge capacity and the first-week Coulomb efficiency in sodium ion batteries.
By accurately controlling the platform area to slope area and specific surface area of the coal-based hard carbon anode material, a coal-based hard carbon anode material with high first-week reversible capacity and first-week Coulomb efficiency was prepared.
While increasing the reversible capacity in the first week, it significantly improved the efficiency of the first week, solving the contradiction between traditional coal-based hard carbon anode materials in this regard.
Smart Images

Figure BDA0005191914320000091 
Figure BDA0005191914320000092 
Figure BDA0005191914320000101
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of secondary batteries, and in particular relates to a coal-based hard carbon negative electrode material and a preparation method and application thereof. Background Art
[0002] In sodium-ion batteries, coal-based negative electrode materials have become a research hotspot due to their excellent conductivity and environmental friendliness and economy. With the growth of demand, higher requirements are placed on the capacity density and initial efficiency of coal-based negative electrode materials. However, when coal-based materials are used as negative electrode materials, they often face the challenge of balancing capacity and initial efficiency. Since the battery capacity can be characterized by the discharge curve, the discharge curve often includes a platform area and a slope area. The slope area is usually related to the adsorption of sodium ions by hard carbon surface defects and the insertion of sodium ions between hard carbon graphite microcrystalline layers, while the platform area is attributed to the filling of sodium in the hard carbon micropores. Therefore, in order to optimize the battery capacity of coal-based negative electrode materials, increasing the proportion of micropores and defects in the hard carbon negative electrode is a feasible direction to optimize the battery capacity. However, since the capacity of the slope area and the platform area is usually related to the defects and micropore filling on the surface of the coal-based material, in order to increase the battery capacity, it is necessary to increase the number of defects and micropores. The increase in the number of defects and micropores will inevitably lead to an increase in the specific surface area, resulting in the formation of more solid electrolyte membranes (SEI membranes) during the first charging process, thereby causing the deterioration of the first efficiency. How to ensure the first efficiency of the battery while increasing the battery capacity has become a major difficulty in current research. Summary of the invention
[0003] In response to the problems existing in the prior art, the coal-based hard carbon negative electrode material provided by the present invention effectively solves the problem that the traditional coal-based materials cannot take into account both the charge and discharge capacity and the first-cycle coulomb efficiency, and obtains a coal-based hard carbon negative electrode material with high first-cycle reversible capacity and first-cycle coulomb efficiency.
[0004] In a first aspect, the present invention provides a coal-based hard carbon negative electrode material, the second cycle discharge curve satisfies 2.50≤N≤4.00, and the specific surface area is selected from 5-200m 2 / g, where N represents the capacity ratio of the platform area to the slope area in the second cycle discharge curve. The platform area refers to the portion of the discharge curve where the voltage is less than 0.1V, and the slope area refers to the portion of the discharge curve where the voltage is greater than 0.1V.
[0005] As some preferred solutions, the second week discharge curve satisfies 3≤N≤4, and the specific surface area of the coal-based hard carbon negative electrode material is selected from 5-50m 2 / g.
[0006] As a further solution, the coal-based hard carbon negative electrode material has a D peak to G peak area ratio of I in the Raman spectrum test. D / I GSelected from 1.70-1.90.
[0007] As a further solution, the total pore volume of the coal-based hard carbon negative electrode material is ≤0.034 cm 3 / g, the proportion of micropore volume with pore diameter less than 2nm to the total pore volume of the material is ≥10%.
[0008] As some preferred solutions, the total pore volume of the coal-based hard carbon negative electrode material is ≤0.034cm 3 / g, the volume of micropores with a pore size of less than 2nm accounts for ≥20% of the total pore volume of the material.
[0009] As some preferred solutions, the total pore volume of the coal-based hard carbon negative electrode material is ≤0.034cm 3 / g, the volume of micropores with a pore size of less than 2nm accounts for ≥30% of the total pore volume of the material.
[0010] In the second aspect, the present invention also provides a method for preparing a coal-based hard carbon negative electrode material using a coal-based material as a raw material, wherein the crushed coal-based material is acid-washed and pre-carbonized, and then steam activated and high-temperature carbonized to obtain a coal-based hard carbon negative electrode material. During the preparation process, the steam activation temperature, steam activation time, activator flow rate, and high-temperature carbonization temperature are regulated to make the specific surface area of the prepared coal-based hard carbon negative electrode material meet S 实 =[0.59EXP(X / 1.305)+24.39EXP(-Y / 2)-20.96]±Z, to obtain a coal-based hard carbon negative electrode material, wherein X=(A-750) / 50+B+C, Y=(D-1300) / 100, 2≤X≤7, A>750, 0≤Y≤3, S 实 is the measured specific surface area, X is the steam activation factor, A is the activation temperature (°C), B is the activation time (h), C is the activator flow rate (ml / min), Y is the high-temperature carbonization factor, and D is the high-temperature carbonization temperature (°C).
[0011] As a further solution, the coal-based material is selected from any one or more of bituminous coal, sub-bituminous coal, anthracite, and lignite.
[0012] As a further scheme, the pickling solution is selected from a combination of two or more of hydrochloric acid, hydrofluoric acid, and nitric acid, and the mass ratio of the pickling solution to the coal-based material is selected from (3-7): 1. After the pickling is completed, the pickled coal-based material is washed with deionized water and the washing liquid is tested. When the pH of the washing liquid is greater than 6, the washing is deemed to be completed and dried.
[0013] As a further solution, the pre-carbonization heating rate is selected from 2°C / min-5°C / min.
[0014] As a further solution, the pre-carbonization temperature is selected from 500-1000°C.
[0015] As a further solution, the pre-carbonization temperature is selected from 600-800°C.
[0016] As a further solution, the pre-carbonization time is selected from 1-5h.
[0017] As a further solution, the pre-carbonization time is selected from 2-4 hours.
[0018] As a further solution, the pre-carbonization is performed under an inert atmosphere.
[0019] As a further solution, the inert atmosphere is selected from any one of argon and nitrogen.
[0020] As a further solution, the activator steam for steam activation is selected from deionized water vapor.
[0021] As a further solution, the steam activation heating rate is selected from 5°C / min-15°C / min.
[0022] As a further solution, the vapor-activated carrier gas is selected from any one of argon and nitrogen.
[0023] As a further solution, the steam activation heating rate is selected from 5°C / min-15°C / min.
[0024] As a further solution, the high-temperature carbonization is carried out in an inert atmosphere, and the inert atmosphere is selected from any one of argon and nitrogen.
[0025] As a further solution, the high temperature carbonization heating rate is selected from 3°C / min-8°C / min.
[0026] As a further embodiment, the cooling temperature is selected from 70°C-25°C.
[0027] As a further solution, the high temperature carbonization time is selected from 2h-6h.
[0028] As some preferred schemes, the activation temperature A is selected from 850℃-1000℃, the activation time B is selected from 1h-3h, the activator flow rate C is selected from 0.5ml / min-3ml / min, and the high-temperature carbonization temperature D is selected from 1300℃-1600℃.
[0029] As some preferred schemes, the activation temperature A is selected from 800°C-900°C, the activation time B is selected from 1h-3h, the activator flow rate C is selected from 0.5ml / min-1ml / min, and the high-temperature carbonization temperature D is selected from 1300°C-1500°C.
[0030] Compared with the prior art, the present invention has at least the following beneficial effects:
[0031] The present invention provides a coal-based hard carbon negative electrode material. By precisely controlling the ratio of the platform area to the slope area and the specific surface area of the coal-based hard carbon negative electrode material, the present invention significantly improves the first-week coulomb efficiency while improving the first-week reversible capacity. This innovative design effectively solves the contradiction between the first-week reversible capacity and the first-week coulomb efficiency of traditional coal-based hard carbon negative electrode materials. In addition, the material has low cost and a simplified preparation process, which makes it have broad prospects in commercial production. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] The accompanying drawings constituting a part of the present invention are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the accompanying drawings:
[0033] Figure 1 This is a SEM image of the coal-based hard carbon negative electrode material prepared in Example 1;
[0034] Figure 2 This is a charge and discharge curve diagram of the coal-based hard carbon negative electrode material prepared in Example 3;
[0035] Figure 3 This is the XRD pattern of the coal-based hard carbon negative electrode material prepared in Example 3;
[0036] Figure 4 This is the Raman spectrum of the coal-based hard carbon negative electrode material prepared in Example 8. DETAILED DESCRIPTION
[0037] In order to facilitate the understanding of the present invention, the present invention will be described more comprehensively below in conjunction with the accompanying drawings. Embodiments of the present invention are given, but the scope of the present invention is not limited thereby.
[0038] Unless otherwise specified, the experimental methods used in the following examples are all conventional methods.
[0039] Unless otherwise specified, the materials, reagents, devices, etc. used in the following examples can be obtained from commercial sources or prepared according to methods in public literature.
[0040] Where values are described herein as a range, it should be understood that such disclosure includes disclosure of all possible sub-ranges within that range, as well as specific values falling within that range, regardless of whether a specific value or a specific sub-range is explicitly stated.
[0041] The following are terms or word definitions, and unless otherwise defined, all technical and scientific terms used herein are
[0042] In this article, the term "theoretical specific surface area" as used herein refers to the specific surface area calculated by S 理
[0043] =[0.59EXP(X / 1.305)+24.39EXP(-Y / 2)-20.96] to calculate the specific surface area.
[0044] In this article, the term "measured specific surface area S" is used herein. 实 " refers to the specific surface area obtained by actual testing of coal-based hard carbon anode materials through BET.
[0045] As used herein, the term "specific surface area" refers to the surface area per unit mass of the coal-based hard carbon negative electrode material.
[0046] In a first aspect, the present invention provides a coal-based hard carbon negative electrode material, the second cycle discharge curve satisfies 2.50≤N≤4.00, and the specific surface area is selected from 5-200m 2 / g, where N represents the capacity ratio of the platform area to the slope area in the second cycle discharge curve. The platform area refers to the portion of the discharge curve where the voltage is less than 0.1V, and the slope area refers to the portion of the discharge curve where the voltage is greater than 0.1V.
[0047] In the discharge curve of the hard carbon negative electrode material of the sodium ion battery, the sodium storage mechanism in the slope area is related to the adsorption of sodium ions by the surface defects of the hard carbon and the insertion of sodium ions in the interlayer of the hard carbon graphite microcrystal; while the platform area is attributed to the filling of sodium in the hard carbon micropores. When the second week discharge curve satisfies 2.50≤N≤4.00, it means that the coal-based hard carbon negative electrode material can provide a higher content of micropores for the filling of sodium ions. At the same time, it also has a considerable graphite microcrystalline structure and disordered carbon to achieve the insertion and storage of sodium ions, thereby fully improving the charge and discharge capacity of the battery; and further, when the second week discharge curve satisfies 2.50≤N≤4.00, we further adjust the specific surface area of the coal-based hard carbon negative electrode material to 5-200m 2 / g, thereby increasing the charge and discharge capacity of the battery while limiting the specific surface area of the coal-based hard carbon negative electrode material, avoiding excessive consumption of sodium ions, and thus optimizing the first coulombic efficiency of the coal-based hard carbon negative electrode material.
[0048] As some preferred solutions, the second week discharge curve satisfies 3≤N≤4, and the specific surface area of the coal-based hard carbon negative electrode material is selected from 5-50m 2 / g, it helps to further increase the proportion of micropores and optimize the specific surface area of coal-based hard carbon negative electrode materials, thereby optimizing the battery charge and discharge capacity and improving the battery's first coulombic efficiency.
[0049] As a further solution, the coal-based hard carbon negative electrode material has a D peak to G peak area ratio of I in the Raman spectrum test. D / I G In Raman spectroscopy, the D peak is usually related to defects in carbon materials, and the appearance of the D peak often indicates the presence of a disordered structure in the material; while the G peak usually indicates that the carbon atom sp 2 The in-plane stretching vibration of the hybrid can be used to provide information on the crystallinity and grain size of the material; when the ratio of the D peak to the G peak area of the coal-based hard carbon negative electrode material is D / I G When selected from 1.70-1.90, it means that the coal-based hard carbon negative electrode material has a higher proportion of defects, so it can effectively improve the slope area capacity of the coal-based hard carbon negative electrode material, and then optimize the charge and discharge capacity of the coal-based hard carbon negative electrode material.
[0050] As some preferred solutions, the total pore volume of the coal-based hard carbon negative electrode material is ≤0.034cm 3 / g, the proportion of micropore volume with pore size <2nm to the total pore volume of the material is ≥10%. The pore size and porosity are also important factors affecting the electrochemical performance of coal-based hard carbon negative electrode materials. The total pore volume of the coal-based hard carbon negative electrode material proposed in this scheme is ≤0.034cm 3 / g, and the proportion of micropore volume with pore diameter <2nm to the total pore volume of the material is ≥10%, which means that the coal-based hard carbon negative electrode material prepared by this scheme has a higher proportion of micropores (2nm) and a higher porosity, thereby enhancing the ability of the coal-based hard carbon negative electrode material to fill sodium ions. Therefore, the coal-based hard carbon negative electrode material exhibits a higher charge and discharge capacity.
[0051] As some preferred solutions, the total pore volume of the coal-based hard carbon negative electrode material is ≤0.034cm 3 / g, the volume of micropores with a pore size of less than 2nm accounts for ≥20% of the total pore volume of the material. When the volume of micropores with a pore size less than 2nm accounts for ≥20% of the total pore volume, it helps to further improve the platform area capacity and optimize the battery performance.
[0052] In the second aspect, the present invention also provides a method for preparing a coal-based hard carbon negative electrode material, which can also be used as a method for designing the preparation condition parameters of a coal-based hard carbon negative electrode material, wherein the crushed coal-based material is acid-washed and pre-carbonized, and then steam activated and high-temperature carbonized to obtain a coal-based hard carbon negative electrode material; during the preparation process, the target coal-based hard carbon negative electrode material is obtained by controlling the difference between [0.59EXP(X / 1.305)+24.39EXP(-Y / 2)-20.96] and the measured specific surface area to be less than 3, thereby realizing the selection of the steam activation temperature, steam activation time, activator flow rate, and high-temperature carbonization temperature parameters, that is, S 实=[0.59EXP(X / 1.305)+24.39EXP(-Y / 2)-20.96]±Z, wherein X=(A-750) / 50+B+C, Y=(D-1300) / 100, 2≤X≤7, A>750, 0≤Y≤3, X is the steam activation factor, A is the activation temperature (°C), B is the activation time (h), C is the activator flow rate (ml / min), Y is the high temperature carbonization factor, and D is the high temperature carbonization temperature (°C).
[0053] There is a certain correlation between the condition parameters in the preparation method and the specific surface area of the obtained coal-based hard carbon negative electrode material. When the steam activation temperature, steam activation time, activator flow rate, and high-temperature carbonization temperature parameters are substituted into [0.59EXP(X / 1.305)+24.39EXP(-Y / 2)-20.96] and the difference between the result of [0.59EXP(X / 1.305)+24.39EXP(-Y / 2)-20.96] and the measured specific surface area is controlled to be less than 3, we can obtain the target coal-based coal. Based on the hard carbon negative electrode material; therefore, we can directly use the preparation condition parameters that satisfy the above correlation to obtain the required target material. At the same time, we can also obtain a method for designing coal-based hard carbon negative electrode material parameters based on the above correlation. By controlling the difference between the result [0.59EXP(X / 1.305)+24.39EXP(-Y / 2)-20.96] and the measured specific surface area to be less than 3, we can also achieve specific selection of steam activation temperature, steam activation time, activator flow rate, and high-temperature carbonization temperature parameters.
[0054] As a further solution, the coal-based material is selected from any one or more of bituminous coal, sub-bituminous coal, anthracite, and lignite.
[0055] As a further scheme, the pickling solution is selected from a combination of two or more of hydrochloric acid, hydrofluoric acid, and nitric acid, and the mass ratio of the pickling solution to the coal-based material is selected from (3-7): 1. After the pickling is completed, the pickled coal-based material is washed with deionized water and the washing liquid is tested. When the pH of the washing liquid is greater than 6, the washing is deemed to be completed and dried.
[0056] As a further solution, the pre-carbonization heating rate is selected from 2°C / min-5°C / min.
[0057] As a further solution, the pre-carbonization temperature is selected from 500-1000°C.
[0058] As a further solution, the pre-carbonization temperature is selected from 600-800°C.
[0059] As a further solution, the pre-carbonization time is selected from 1-5h.
[0060] As a further solution, the pre-carbonization time is selected from 2-4 hours.
[0061] As a further solution, the pre-carbonization is performed under an inert atmosphere.
[0062] As a further solution, the inert atmosphere is selected from any one of argon and nitrogen.
[0063] As a further solution, the activator steam for steam activation is selected from deionized water vapor.
[0064] As a further solution, the vapor-activated carrier gas is selected from any one of argon and nitrogen.
[0065] As a further solution, the steam activation heating rate is selected from 5°C / min-15°C / min.
[0066] As a further solution, the high-temperature carbonization is carried out in an inert atmosphere, wherein the inert atmosphere is selected from any one of argon and nitrogen.
[0067] As a further solution, the high temperature carbonization heating rate is selected from 3°C / min-8°C / min.
[0068] As a further solution, the high temperature carbonization time is selected from 2h-6h.
[0069] As some preferred schemes, the activation temperature A is selected from 850℃-1000℃, the activation time B is selected from 1h-3h, and the activator flow rate C is selected from 0.5ml / min-3ml / min, which helps to form more defects and more and deeper pores. At the same time, the control of the activator flow rate to 0.5ml / min-3ml / min can also effectively control the pore diameter, providing a better foundation for subsequent high-temperature carbonization. On this basis, the high-temperature carbonization temperature D is selected from 1300℃-1600℃, which helps to further improve the optimization effect of temperature on pore diameter.
[0070] As some preferred schemes, the activation temperature A is selected from 800°C-900°C, the activation time B is selected from 1h-3h, the activator flow rate C is selected from 0.5ml / min-1ml / min, and the high-temperature carbonization temperature D is selected from 1300°C-1500°C. In the process of steam activation of coal-based hard carbon negative electrode materials, when A is selected from 800℃-900℃, since the steam activation process is an endothermic reaction, the activation temperature of 800℃-900℃ helps to promote the reaction rate and form more pores; at the same time, when the activation time is selected from 1h-3h and the activator flow rate is selected from 0.5ml / min-1ml / min, more deep pores and lower specific surface area can be obtained, which lays a good foundation for high-temperature carbonization. Therefore, the high-temperature carbonization temperature D can be selected from 1300℃-1500℃. Therefore, the activation temperature A is selected from 800℃-900℃, the activation time B is selected from 1h-3h, the activator flow rate C is selected from 0.5ml / min-1ml / min, and the high-temperature carbonization temperature D is selected from 1300℃-1500℃, which helps to obtain coal-based hard carbon negative electrode materials with higher charge and discharge capacity.
[0071] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application and do not represent all possible embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.
[0072] The chemical raw materials involved in the following examples and comparative examples are all prior art and are commercially available. The experimental devices, test devices, etc. involved in the following examples and comparative examples are all conventional devices in the art, without special requirements and limitations.
[0073] Example 1
[0074] The preparation steps of coal-based hard carbon negative electrode material are as follows:
[0075] S1: 30 g of bituminous coal raw material particles were ball-milled to a particle size of Dv50 = 5 μm, 4 mol / L hydrochloric acid, 4 mol / L nitric acid, and 10% hydrofluoric acid were mixed in a volume ratio of 3:1:2, and then 30 g of the crushed bituminous coal raw material was pickled with 120 g of the mixed solution. After the pickling, it was washed with deionized water and then filtered until the filtrate met the pH>6, which was considered to be the end of water washing. It was then dried for 12 hours, and under the protection of a nitrogen atmosphere, the temperature was raised to 750°C at a heating rate of 3°C / min for pre-carbonization for 3 hours to obtain a coal-based hard carbon negative electrode material matrix;
[0076] S2: Using nitrogen as carrier gas, water vapor was introduced to activate the coal-based hard carbon negative electrode material matrix in a tubular furnace. The temperature was raised to 900°C at a heating rate of 10°C / min for 1h, and the activator flow rate was 1ml / min.
[0077] S3: Under a nitrogen atmosphere, the steam-activated coal-based hard carbon negative electrode material matrix is activated by a tubular furnace, the temperature is raised to 1500°C at a rate of 5°C / min, the heat preservation time is 3h, and the bituminous coal-based hard carbon negative electrode material is obtained.
[0078] Example 2-16
[0079] Some parameters in Example 1 were changed, and the parameter details are shown in Table 1. The remaining preparation steps and methods were the same as in Example 1.
[0080] Comparative Example 1
[0081] The specific steps and preparation method are the same as those in Example 1, except that the second cycle charge and discharge curve of the prepared coal-based hard carbon negative electrode material satisfies N=1.77. The specific preparation parameters are shown in Table 1.
[0082] Comparative Example 2
[0083] The specific steps and preparation method are the same as those in Example 1, except that the specific surface area of the prepared coal-based hard carbon negative electrode material is greater than 200 m 2 / g, the specific preparation parameters are shown in Table 1.
[0084] Performance Testing
[0085] Electrochemical performance test: The bituminous coal-based hard carbon negative electrode material was used as the negative electrode material powder of the button battery, and the negative electrode sheet was prepared according to the ratio of main material: CMC: SP = 95:5:5. The metal sodium sheet was used as the positive electrode, and 1mol / LNaPF6 / EC+DEC (1:1) was used as the electrolyte. The CR2032 button battery was assembled in the glove box, and the contents of H2O and O2 in the glove box were ensured to be <0.1ppm throughout the process. The CR2032 button battery was tested using the Blue Electric Battery Test System, and the charge and discharge test was performed at a current density of 0.1C. The discharge cut-off voltage was 0V, and the charge cut-off voltage was 2.0V. The test obtained the first-week reversible capacity and first-week coulomb efficiency of the material.
[0086] First cycle coulombic efficiency = (electricity released during the first discharge / electricity stored during the first charge) × 100%. Experimental parameters of Examples 1-16 and Comparative Examples 1-2 are shown in Table 1, and test results of Examples 1-16 and Comparative Examples 1-2 are shown in Table 2.
[0087] Table 1
[0088]
[0089] Table 2
[0090]
[0091]
[0092] It can be observed from Examples 1-16 and Comparative Examples 1-2 that, on the one hand, Examples 1-16 exhibited first-week reversible capacity and first-week coulombic efficiency far superior to those of Comparative Examples 1-2, indicating that when the second-week discharge curve of the coal-based hard carbon negative electrode material satisfies 2.50≤N≤4.00, and the specific surface area is selected from 5-200 m 2 / g, the coal-based hard carbon negative electrode material can further optimize the first coulombic efficiency while ensuring the improvement of the reversible capacity in the first week.
[0093] Specifically, it can be observed from Example 1 and Comparative Example 1 that when the ratio of the platform area / slope area of the second-week discharge curve of the coal-based hard carbon negative electrode material does not satisfy 2.50≤N≤4.00, Comparative Example 1 exhibits a first-week reversible capacity far lower than that of Example 1. This may be because when N is less than 2.5, the coal-based hard carbon negative electrode material may not be able to provide sufficient micropores to satisfy the filling of sodium ions, and thus the first-week reversible capacity of Comparative Example 1 is affected.
[0094] On the other hand, it can be observed from Example 1 and Comparative Example 2 that when the specific surface area of the coal-based hard carbon negative electrode material is higher than 200 m 2 / g, the first week coulomb efficiency in comparative example 2 was significantly affected. This is because when the specific surface area of the coal-based hard carbon negative electrode material is higher than 200m 2 / g, more sodium ions are consumed, resulting in low coulombic efficiency in the first week, so it is necessary to control the specific surface area.
[0095] From Examples 1-3 and 4-9, we can observe an interesting phenomenon that when the second-week discharge curve satisfies 3≤N≤4, Example 1-3 exhibits a better first-week reversible capacity than Example 4-9. This may be because when the second-week charge and discharge curve satisfies 3≤N≤4, there is a higher proportion of micropores in the coal-based hard carbon negative electrode material. These micropores can provide sufficient filling space for sodium ions during the battery cycle, thereby improving the first-week reversible capacity of the coal-based hard carbon negative electrode material.
[0096] On the other hand, by comparing Examples 1-9, 11-16 with Example 10, we can also observe that when the specific surface area of the coal-based hard carbon negative electrode material is selected from 5-50 m 2 / g, Examples 1-9, 11-16 showed better first-week coulombic efficiency than Example 10, which may be due to the fact that when the specific surface area of the coal-based hard carbon negative electrode material is selected from 5-50m 2 / g, in the process of first forming SEI film, we can retain more sufficient electrolyte and sodium ions to improve the first efficiency, so Examples 1-9, 11-16 show better first-week Coulomb efficiency than Example 10.
[0097] In coal-based hard carbon negative electrode materials, the proportion of micropores less than 2 nm will affect the platform area capacity, and thus affect the first-week reversible capacity. From Examples 1-5, it can be observed that Examples 1-7 and 11-16 show better first-week reversible capacity than Examples 8-10, and Examples 1-5 show better first-week reversible capacity than Examples 6-7 and 11-16. Therefore, from Examples 1-16, it can be further preferred that the micropore volume proportion of the coal-based hard carbon negative electrode material is greater than 20%. Furthermore, according to Examples 1-7 and 11-16, it can be further preferred that the micropore volume proportion of the coal-based hard carbon negative electrode material is greater than 30%.
[0098] In addition, Examples 1-2 and 3-5 further discussed the activation temperature, activation time, activator flow rate and high-temperature carbonization temperature. Examples 1-2 as a whole showed better first-week reversible capacity and micropore ratio than Examples 3-5, and showed a higher platform capacity (greater than 3.5) in the ratio of platform capacity to slope capacity in the second-week charge-discharge curve. This may be because when A is selected from 800°C-900°C, since the steam activation process is an endothermic reaction, an activation temperature higher than 800°C helps to promote the reaction rate and form more pores (such as Figure 1 ); At the same time, when the activation time is selected from 1h-3h and the activator flow rate is selected from 0.5ml / min-1ml / min, more deep pores and a lower measured specific surface area S can be obtained. 实 , thus laying a good foundation for high-temperature carbonization. At this time, the high-temperature carbonization temperature D is selected to be 1300℃-1500℃, which can give full play to the high-temperature carbonization effect and obtain a coal-based hard carbon negative electrode material with excellent charge and discharge capacity.
[0099] It can be observed from Examples 1 and 11 that when the particle size of the crushed bituminous coal is selected to be Dv50=5, Example 1 exhibits a higher micropore ratio than Example 11, and at the same time, the micropore ratio of the medium I D / I G It is 1.85. This may be because when the bituminous coal particle size is selected from Dv50=5-15μm, the particle size that satisfies Dv50=5-15μm helps to further coordinate with the steam to achieve activation of the coal-based hard carbon negative electrode material matrix, thereby increasing the number of pores and defects. Therefore, Example 1 exhibits better first-week reversible capacity than Example 11.
[0100] In the step of preparing coal-based hard carbon negative electrode materials, the role of pre-carbonization is to initially form pores in the coal-based material to facilitate subsequent steam activation. It can be seen from Example 1 and Examples 12-13 that when the pre-carbonization time is 3 hours, Example 1 shows a higher total pore volume and micropore volume ratio than Examples 12-13, and thus shows a higher first-week reversible capacity. This may be because the 3-hour pre-carbonization time helps to form a higher number of pore prototypes, thereby laying a good foundation for subsequent steam activation; while Examples 1 and Examples 14-15 demonstrate the role of pre-carbonization temperature. When the pre-carbonization temperature is 750°C, it can prompt the coal-based material to form more and more evenly distributed pores, which also lays the foundation for subsequent steam activation. Therefore, Example 1 shows a higher first-week reversible capacity than Examples 12-15.
[0101] Although the embodiments of the present invention have been shown and described above, it is understood that the above embodiments are exemplary and cannot be understood as limiting the present invention. Those skilled in the art may change, modify, replace and deform the above embodiments within the scope of the present invention. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples without contradiction.
Claims
1. A coal-based hard carbon negative electrode material, characterized in that: The discharge curve of the second cycle satisfies 2.50≤N≤4.00, and the specific surface area is selected from 5-200m 2 / g, where N represents the capacity ratio of the platform area to the slope area in the second cycle discharge curve. The platform area refers to the portion of the discharge curve where the voltage is less than 0.1V, and the slope area refers to the portion of the discharge curve where the voltage is greater than 0.1V.
2. The coal-based hard carbon negative electrode material according to claim 1, characterized in that: The second week discharge curve satisfies 3≤N≤4, and the specific surface area of the coal-based hard carbon negative electrode material is selected from 5-50m 2 / g.
3. The coal-based hard carbon negative electrode material according to claim 1, characterized in that: In the Raman spectrum test of the coal-based hard carbon negative electrode material, the ratio of the D peak to the G peak area is D / I G Selected from 1.70-1.
90.
4. The coal-based hard carbon negative electrode material according to claim 1, characterized in that: The total pore volume of the coal-based hard carbon negative electrode material is ≤0.034 cm 3 / g, the proportion of micropore volume with pore diameter <2nm to the total pore volume of the material is ≥10%; Preferably, the total pore volume of the coal-based hard carbon negative electrode material is ≤0.034 cm 3 / g, the proportion of micropore volume with pore diameter <2nm to the total pore volume of the material is ≥20%; Preferably, the total pore volume of the coal-based hard carbon negative electrode material is ≤0.034 cm 3 / g, the volume of micropores with a pore size of less than 2nm accounts for ≥30% of the total pore volume of the material.
5. A method for preparing a coal-based hard carbon negative electrode material, characterized in that: The coal-based hard carbon anode material is obtained by acid washing and pre-carbonizing the crushed coal-based material, followed by steam activation and high-temperature carbonization. During the preparation process, the preparation parameters are controlled to meet S 实 =[0.59EXP(X / 1.305)+24.39EXP(-Y / 2)-20.96]±Z, to obtain a coal-based hard carbon negative electrode material, wherein X=(A-750) / 50+B+C, Y=(D-1300) / 100, 2≤X≤7, A>750, 0≤Y≤3, S 实 is the measured specific surface area, X is the steam activation factor, A is the activation temperature (℃), B is the activation time (h), C is the activator flow rate (ml / min), Y is the high-temperature carbonization factor, and D is the high-temperature carbonization temperature (℃).
6. The method for preparing a coal-based hard carbon negative electrode material according to claim 5, characterized in that: The raw material of the coal-based hard carbon negative electrode material is selected from any one or more of bituminous coal, sub-bituminous coal, anthracite, and lignite; The pickling solution is selected from a combination of two or more of hydrochloric acid, hydrofluoric acid, and nitric acid. The mass ratio of the pickling solution to the coal-based material is selected from (3-7):
1. After the pickling is completed, the pickled coal-based material is washed with deionized water and the washing liquid is tested. When the pH of the washing liquid is greater than 6, the washing is considered to be completed and dried.
7. The method for preparing a coal-based hard carbon negative electrode material according to claim 5, characterized in that: The pre-carbonization heating rate is selected from 2°C / min-5°C / min; The pre-carbonization temperature is selected from 500-1000°C; Preferably, the pre-carbonization temperature is selected from 600-800°C; The pre-carbonization time is selected from 1-5h; Preferably, the pre-carbonization time is selected from 2-4h; Preferably, the pre-carbonization is carried out under an inert atmosphere; The inert atmosphere is selected from any one of argon and nitrogen.
8. The method for preparing a coal-based hard carbon negative electrode material according to claim 5, characterized in that: The steam activated activator steam is selected from deionized water vapor; The steam activation heating rate is selected from 5°C / min-15°C / min; The steam activated carrier gas is selected from any one of argon and nitrogen; The high temperature carbonization heating rate is selected from 3°C / min-8°C / min, the high temperature carbonization time is selected from 2h-6h, and the cooling temperature is selected from 70°C-25°C.
9. The method for preparing a coal-based hard carbon negative electrode material according to claim 5, characterized in that: The activation temperature A is selected from 850°C-1000°C, the activation time B is selected from 1h-3h, the activator flow rate C is selected from 0.5ml / min-3ml / min, and the high-temperature carbonization temperature D is selected from 1300°C-1600°C.
10. The method for preparing a coal-based hard carbon negative electrode material according to claim 5, characterized in that: The activation temperature A is selected from 800°C-900°C, the activation time B is selected from 1h-3h, the activator flow rate C is selected from 0.5ml / min-1ml / min, and the high-temperature carbonization temperature D is selected from 1300°C-1500°C.
Citation Information
Cited By
Sodium-ion battery design method and system and sodium-ion battery
CN120545493A
Coal-based porous carbon, preparation method and application
CN122444180A